Correction: Protective effects of Xinji'erkang on myocardial infarction induced cardiac injury in mice - Juan Hu; Yong-xue Zhang; Li Wang; Ling Ding; Guang-yao Huang; Guo-wei Cai; Shan Gao (BMC, 2023)
An amendment to this paper has been published and can be accessed via the original article.